In vivo imaging of orthotopic prostate cancer with far-red gene reporter fluorescence tomography and in vivo and ex vivo validation - Lu, Yujie (Society of Photo-Optical Instrumentation Engineers, 2013)
Fluorescence gene reporters have recently become available for excitation at far-red wavelengths, enabling opportunities for small animal in vivo gene reporter fluorescence tomography (GRFT). We employed multiple projections of the far-red fluorescence gene reporters IFP1.4 and iRFP, excited by a point source in transillumination geometry in order to reconstruct the location of orthotopically implanted human prostate cancer (PC3), which stably expresses the reporter. Reconstruction was performed using a linear radiative-transfer-based regularization-free tomographic method. Positron emission tomography (PET) imaging of a radiolabeled antibody-based agent that targeted epithelial cell adhesion molecule overexpressed on PC3 cells was used to confirm in vivo GRFT results. Validation of GRFT results was also conducted from ex vivo fluorescence imaging of resected prostate tumor. In addition, in mice with large primary prostate tumors, a combination of GRFT and PET showed that the radiolabeled antibody did not penetrate the tumor, consistent with known tumor transport limitations of large ([Formula: see text]) molecules. These results represent the first tomography of a living animal using far-red gene reporters.